Latency Inflation with MPLS-based Traffic Engineering - Pathak, Abhinav; Zhang, Ming; Hu, Y. Charlie; Mahajan, Ratul; Maltz, Dave (IMC'11, Berlin, Germany., 2011)
While MPLS has been extensively deployed in recent years, little is known about its behavior in practice. We examine the performance of MPLS in Microsoft’s online service network (MSN), a well-provisioned multi-continent production network connecting tens of data centers. Using detailed traces collected over a 2-month period, we find that many paths experience significantly inflated latencies. We correlate occurrences of latency inflation with routers, links, and DC-pairs. This analysis sheds light on the causes of latency inflation and suggests several avenues for alleviating the problem.